Myanmar energy consumption surveys. (Metro Manila, Philippines Asian Development Bank, 2017)
Myanmar has one of the fastest growing economies in Asia, yet its potential is severely constrained by limited energy infrastructure. The limited availability of modern energy services and infrastructure has resulted in Myanmar having one of the lowest per capita energy consumption rates in the world.
Keywords: Economics development -- Myanmar; Electronic books